2000
DOI: 10.1007/s002100000256
|View full text |Cite
|
Sign up to set email alerts
|

Further pharmacological analysis of the orphan 5-HT receptors mediating feline vasodepressor responses: close resemblance to the 5-HT 7 receptor

Abstract: It has been suggested that the late hypotensive response to serotonin (5-hydroxytryptamine; 5-HT) in vagosympathectomised cats, being potently mimicked by 5-carboxamidotryptamine (5-CT), not modified by ketanserin and blocked by methiothepin or methysergide, is mediated by '5-HT1-like' receptors. Nevertheless, current guidelines for 5-HT receptor classification refer to this receptor as an orphan receptor. Thus, the present study set out to reanalyse the above suggestion in terms of the classification schemes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Accordingly, the above rank order of agonist potency (tryptamine fingerprint) parallels that reported at both the cloned 5-HT 7 receptor (e.g. Lovenberg et al 1993;Shen et al 1993) and the functional 5-HT 7 receptors mediating: (1) external carotid vasodilatation in dogs (Villalón et al 1997a); (2) hypotension in rats (De Vries et al 1997); and (3) tachycardia (Villalón et al 1997b) and hypotension (Villalón et al 2000) in cats. In contrast, the above tryptamine fingerprint differs from that reported at cloned 5-ht 6 receptors (5-MeO-T > 5-HT > 5-CT; Monsma et al 1993).…”
Section: Generalsupporting
confidence: 51%
See 3 more Smart Citations
“…Accordingly, the above rank order of agonist potency (tryptamine fingerprint) parallels that reported at both the cloned 5-HT 7 receptor (e.g. Lovenberg et al 1993;Shen et al 1993) and the functional 5-HT 7 receptors mediating: (1) external carotid vasodilatation in dogs (Villalón et al 1997a); (2) hypotension in rats (De Vries et al 1997); and (3) tachycardia (Villalón et al 1997b) and hypotension (Villalón et al 2000) in cats. In contrast, the above tryptamine fingerprint differs from that reported at cloned 5-ht 6 receptors (5-MeO-T > 5-HT > 5-CT; Monsma et al 1993).…”
Section: Generalsupporting
confidence: 51%
“…Apart from the implications discussed below, these data indicate that the pharmacological profile of the canine internal carotid vasodilator 5-HT receptors is similar to that reported for the 5-HT 7 receptors mediating cardiovascular responses in vivo (e.g. Hoyer et al 1994;Martin 1994;De Vries et al 1997;Villalón et al 1997bVillalón et al , 2000.…”
Section: Generalmentioning
confidence: 59%
See 2 more Smart Citations
“…In the guinea pig hippocampus, Thomas et al (1999) reported that 5-HT agonists displaced [ 3 H]-5-CT binding to membranes with the following rank order of af®nity: 5-CT 4 5-HT 4 8-OH-DPAT, indicating that 5HT 7 receptors were present in this tissue. A similar rank order of potency of 5-HT receptor agonists have been described in tissues containing 5-HT receptors by Villalon et al (2000) and Bacon and Beck (2000). In the present study, effects of the abovenamed selective agonists for 5-HT 7 receptors (in addition to agonists activating the other 5-HT receptor subtypes) were tested.…”
Section: Discussionmentioning
confidence: 54%